Thirst #4 - Pike, Christopher 1961- (New York : Simon Pulse, 2009)
Chronicles the events in the life of Alisa, a five-thousand-year-old vampire.
v. 1. The last vampire ; Black blood ; Red dice -- v. 2. Phantom ; Evil thirst ; Creatures of forever -- v. 3. The eternal dawn -- v. 4. The shadow of death
Keywords: Vampires -- Fiction; Fiction